Ecological Existentialism in Echoes: Existence of Human Life and Nature (Kaumodaki: Journal of Multidisciplinary Studies, 2024)
This research article delves into the philosophical foundations of the novel, Echoes, which centers on the central character’s pursuit, as a teacher, of goodness over greatness and his existential quest for meaning. With the objective of examining the novel’s themes and narrative structure from eco-existential point of view, the study investigates the principles of ecological existentialism and the interplay between human existence and the natural world. Central to this exploration, as the research questions, are the concepts of solitude, freedom, and Karma, which the author employs to advocate for existentialism within an ecological framework. By employing ecocriticism and existentialism as theoretical lenses, the article elucidates how the novel portrays the co-existential relationship between humanity and ecology, emphasizing human responsibility and the freedom to imbue life with meaning. This analysis is significant in fostering environmental values and highlighting the interconnectedness of human existence and the natural environment. The study underscores the novel’s potential to illuminate paths towards ecological harmony and deepen understanding of existential philosophy, particularly as it pertains to questions of individuality, freedom, and the search for meaning in the context of environmental ethics. Ultimately, it advocates for a holistic approach to existence that acknowledges the profound influence of ecological factors on human life and underscores the importance of aligning existential values with environmental stewardship.